2020
DOI: 10.1177/0033354920927845
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Recommendations for Primary Care–Based Screening for Latent Tuberculosis Infection in California

Abstract: Objective Targeted testing and treatment of persons with latent tuberculosis infection (LTBI) is a critical component of the US tuberculosis (TB) elimination strategy. In January 2016, the California Department of Public Health issued a tool and user guide for TB risk assessment (California tool) and guidance for LTBI testing, and in September 2016, the US Preventive Services Task Force (USPSTF) issued recommendations for LTBI testing in primary care settings. We estimated the epidemiologic effect of adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Additional guidance, such as the California TB Risk Assessment tool, recommends LTBI testing and treatment for all non-US-born individuals, individuals with immunosuppressive conditions or taking immunosuppressive therapy, and individuals who have had contact with someone with infectious TB disease during their lifetime [22]. Recent modeling has demonstrated that adherence to such approaches could substantially reduce the burden of TB disease, reducing incidence by 40% [23].…”
Section: Plos Onementioning
confidence: 99%
“…Additional guidance, such as the California TB Risk Assessment tool, recommends LTBI testing and treatment for all non-US-born individuals, individuals with immunosuppressive conditions or taking immunosuppressive therapy, and individuals who have had contact with someone with infectious TB disease during their lifetime [22]. Recent modeling has demonstrated that adherence to such approaches could substantially reduce the burden of TB disease, reducing incidence by 40% [23].…”
Section: Plos Onementioning
confidence: 99%
“…Future predictive models incorporating predicted birth in HTBIC along with other elements that may predict TB activation (immunosuppression, etc) may improve the predictive power and reduce the number needed to be screened overall. Even testing only 25% of eligible patients in primary care encounters could prevent a substantial amount of TB cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We summarize key results of NEEMA TB modeling activities that have been published or publicly presented and that have programmatic implications for which populations to test, which test to use, and which treatments are most cost effective. [17][18][19][20][21][22][23][24][25] A consensus of NEEMA modeling to date concurs with the aforementioned guidelines and suggests that, for greatest effectiveness and cost effectiveness, targeted testing policies should focus on LTBI testing and treatment among non-US-born persons and persons with HIV, respectively. Testing with an IGRA appears to be most cost effective.…”
Section: Current Guidelinesmentioning
confidence: 99%
“…23 A 23% increase in LTBI testing and treatment of all USPSTF-recommended populations at high risk 6 in California could prevent approximately 40% of new TB cases in the first decade post-implementation, with targeted testing and treatment of non-US-born persons having the greatest impact. 24…”
Section: Which Populations To Test and Treatmentioning
confidence: 99%